Korelasi Sikap, Minat, dan Motivasi Belajar dengan Pengetahuan Sejarah Lokal Lampung - Siska, Yulia (Mimbar Sekolah Dasar, 2018)
This study aims to describe the significant relationship between attitudes, interests, and motivations with students’ knowledge of local history. This research employed a quantitative approach with regression analysis. The population of this study was the 5th grade students of an Elementary School in Bandarlampung. The number of the sample was 53 students. The technique used was purposive sampling. The research instrument is a scale of motivation, interests, attitudes, and knowledge of local history. In analyzing the data the three predictors regression technique was used. The results showed that: (1) There is no relationship between attitude towards Local History Lesson (X1) with the Local History Knowledge (Y); (2) There is no correlation between Interest in Local History Lesson (X2) with Local History Knowledge (Y); (3) There is a significant relationship between the Motivation of Learning Local History (X3) with Local History Knowledge (Y); and (4) There are a significant relationship between Attitude (X1), Interests (X2), and Local Historical Learning Motivation (X3) along with Local History Knowledge (Y) of the 5th grade students of an Elementary School in Bandarlampung.